The Concept of Islamic Education Based on the Perspective of Imam Al-Ghazali - Azizah, Khusnul Nur; Abidin, Zainal (Al-Munawwarah: Journal of Islamic Education, 2025)
Education in Indonesia, while not entirely based on Islamic principles, is still deeply influenced by the values of Islamic teachings. Challenges arise when the education system produces educated individuals who lack moral and ethical qualities. This study aims to analyze Imam Al-Ghazali’s thoughts on Islamic education and its implications in the context of modern education. The method used in this research is library research, which reviews various sources related to Al-Ghazali’s ideas. The findings reveal that Al-Ghazali emphasizes the importance of education that not only focuses on worldly aspects but also on character and moral development. Additionally, this study finds that a holistic approach to education, encompassing spirituality and morality, is essential for creating balanced and responsible individuals. Thus, education understood from Al-Ghazali’s perspective can offer solutions to address moral issues in contemporary education, fostering a generation that is not only knowledgeable but also possesses good character. This research contributes to enriching the understanding of Islamic educational values and their relevance in creating a more ethical and civil society.